LITERARY CONNECTION AND ITS DEFINITION (ON THE EXAMPLE OF TURKISH-INDIAN LITERATURE) (Journal of Oriental Studies, 2019)
«The key to the exchange of ideas between the intellectual treasures of different cultures and na tions that change the world is the literary space», as Goethe said, despite today’s relative problems of world literature, its importance is increasing. Because of increasing globalization, the ability to more widely show and spread their culture is an important factor in literature. Since literature is one, of the legacies that shows the country’s history and its value, the article examines the views of political figures and scholars of the TurkIndian peoples, such as M. Gandhi, Mustafa Kemal AtaTurk, D. Kunayev, who understood the value of the worldview for the country. In addition, in the  studied scientific  work based on Turkish and Indian literature, the concept of literary connections will  be analyzed in the consonance  of the spiritual world of the people with a literary and cultural connection in the TurkicIndian ideological heritage, whose history has been shaped for many centuries. The continuity of the TurkicIndian literary ties with a centuriesold history is of particular importance in the history of the development of spiritual culture and in the artistic development of literature. Therefore, the study of literary relations between countries will become a source for the expansion of scientific and theoretical traditions of the TurkIndian cultural relations.Key words: Literary communication, Turkey, India, heritage, value, consonance, history.